The Relative contribution of Professional Motivation and Self-Management in Prediction Decision-Making among Administrators Positions at Jadara University - Jordan - Abu Rashed, Marwa Marwan; Tashtoush, Rami Abdullah (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the level of professional motivation, the level of self-management, and the level of decision-making ability of administrators at Jadara University. The study sample consisted of (108) administrators and administrators from Jadara University in Jordan, who were selected intentionally in the first semester 2020/2021. The two researchers developed and used a scale prepared by Othman (2015), and to ensure its validity and reliability. The scale in its initial form consisted of (40) items. level of ambition, perceived competence. The results of the study showed that the arithmetic averages for the level of professional motivation came to a medium degree. The level of self-management came to a medium degree, and the level of decision-making came to a medium degree. The results also showed that there is a relative contribution of professional motivation and self-management in predicting decision-making among the holders of administrative positions at Jadara University. The study recommended the need to pay attention to the relative contribution of professional motivation and self-management in predicting decision-making among the occupants of administrative positions, and to develop an integrated system to increase motivation towards work and achievement because it reflects on the goal of the presence of administrative leaders in universities.